Hypoglycemic effect of rosmarinic acid-rich infusion (RosCE) from Origanum vulgare in alloxan-induced diabetic rats. Issue 17 (1st September 2022) - Silva, Márcio L. A. e; Lucarini, Rodrigo; dos Santos, Fransergio F.; Martins, Carlos H. G.; Pauletti, Patricia M.; Januario, Ana H.; Santos, Mario Ferreira Conceição; Cunha, Wilson R.
Abstract: Origanum vulgare, known for its medicinal value, is officially accepted in many countries. The flowers and leaves are used globally in homeopathy. In Brazilian folk medicine, O. vulgare has been used to treat diabetes mellitus. This study evaluated the hypoglycemic activity of an infusion extract (RosCE) of commercially available O. vulgare leaves in alloxan-induced diabetic rats. Oral administration of RosCE resulted in the reduction of blood glucose levels after the first day of treatment, compared to the diabetic control group. These results showed that RosCE displays hypoglycemic activity, which may be due to the combined effect of rosmarinic acid, and other minor compounds. Reversed phase-high performance liquid chromatography-diode array detection was used to identify and quantify the major constituents of RosCE. This study presents evidence that supports the folkloric use of O. vulgare for the treatment of hyperglycemia, confirming the use of its infusion as an antidiabetic herbal medicine. Graphical Abstract: UF0001